Prevalence and related factors of compassion fatigue among registered nurses and nursing students during the internship: a systematic review and meta-analysis - Lijuan Yi; Suwen Hu; Mengqi Liao; Liang Cheng; Yi Liu; Xu Tian; Maria F. Jiménez-Herrera (BMC Nursing)
Abstract Background Compassion fatigue impacts nurses’ well-being and work efficiency. Extensive research has explored its prevalence, but evidence regarding related factors is broadly categorized and lacks descriptive data. There’s also a lack of systematic reviews on compassion fatigue among nursing students during internships. Objectives To synthesize evidence on the levels and factors of compassion fatigue among nurses and nursing students during internships. Methods This systematic review is registered with PROSPERO (ID CRD42023444173). Literature searches were conducted in five databases (Cochrane Library, PubMed, EMBASE, CNKI, and WanFang) up to November 30, 2022, with updates planned until January 17, 2024, if necessary. Inclusion criteria covered studies reporting data on the prevalence and related factors of compassion fatigue or its dimensions, burnout and secondary traumatic stress, among registered nurses or nursing students during internships. Independent study selection, quality assessment, and data extraction were performed. The Agency for Healthcare Research and Quality tool was used for critical appraisal of study quality. Random-effects model analyses were conducted using Stata 17.0 to pool data on prevalence rates and mean scores of compassion fatigue. When comprehensive data on compassion fatigue were unavailable, its dimensions were analyzed for both prevalence and mean scores. Results Our review included 196 studies (73,034 nurses and 4,551 nursing students). For nurses, pooled mean scores for burnout and secondary traumatic stress were 26.81 (95% CI 26.28 to 27.35) and 25.88 (95% CI 25.39 to 26.37), respectively. For nursing students during internships, pooled mean scores were 29.16 (95% CI 26.95 to 31.37) and 25.64 (95% CI 20.95 to 30.34), respectively. Subgroup analyses revealed that post-COVID-19 pandemic, nurses exhibited higher compassion fatigue, especially in ICU or emergency departments. Evidence from 93 studies suggested that nurses’ burnout and secondary traumatic stress are both influenced by work environment, social support, job satisfaction, workload, and psychological capital (moderate to low-certainty evidence). For nursing students, psychological capital plays a significant role (moderate to low-certainty evidence). Conclusions Both registered nurses and nursing students experience moderate compassion fatigue. Work environment, social support, job satisfaction, workload, and psychological capital are key factors associated with burnout and secondary traumatic stress in registered nurses. For nursing students, psychological capital plays a similarly significant role. Given that this is the first systematic review to explore these factors among nursing students, further research is essential to deepen understanding and develop effective interventions.